Probing the highly transparent and conducting SnOx/Au/SnOx structure for futuristic TCO applications. Issue 35 (21st March 2016) - Sharma, V.; Vyas, R.; Bazylewski, P.; Chang, G. S.; Asokan, K.; Sachdev, K.
Abstract : A SnO x /Au/SnO x transparent conductive oxide (TCO) multilayered film was fabricated with a total thickness of 75 nm using both e-beam and thermal evaporation techniques. Abstract : A SnO x /Au/SnO x transparent conductive oxide (TCO) multilayered film was fabricated with a total thickness of 75 nm using both e-beam and thermal evaporation techniques. X-ray diffraction confirms the amorphous nature of SnO x with a crystalline peak attributed to the presence of diffraction from the Au (111) plane. The morphological studies using atomic force microscopy (AFM) and scanning electron microscopy (SEM) revealed a smooth top layer of the sandwich structure. A Rutherford backscattering spectrum has been used to probe the thickness of individual TCO layers, and reveals an oxygen deficient structure in the SnO x layer. X-ray absorption spectroscopy (XAS) and X-ray emission spectroscopy (XES) measurements confirm the formation an SnO-rich phase and the presence of oxygen vacancies. The specimen exhibited resistivity and sheet resistance of 3.9 × 10 −4 Ω cm and 52 Ω sq. −1, respectively, with an optical transparency of 83% beyond 475 nm. The superior parameters exhibited by this stacked multilayer are due to relatively lower oxygen concentration in the tin oxide layer, and it is therefore proposed as a necessary ingredient to increase the overall conductivity in metal oxide multilayer thin films.